Gender Difference in Long- and Short-Term Outcomes of Off-Pump Coronary Endarterectomy - Sabzi, Feridoun (Ann Card Anaesth, 2020)
BACKGROUND: The role of gender in the selection of the most effective method for treatment of patients with diffused coronary artery diseases remains a matter of debate. This study thus evaluated the effect of gender on long- and short-term outcomes of off-pump coronary endarterectomy (CE). METHODS: This was a single-center retrospective study of patients who had undergone coronary artery bypass graft (CABG). The patients were divided into two groups, the CABG and the CABG + CE group, and further stratified into male and female. Long-term survival for each group was estimated by Kaplan–Meier analysis with log-rank testing. In addition, Cox regression analyses of each gender were also carried out to identify the predictors of the primary and secondary endpoints. RESULTS: Overall, 25.8% of the patients were female. Diseased vessels were not statistically different in the two groups – men and women. There was no significant difference in postoperative outcomes between males and females in the CABG and CABG + CE groups. There was no significant difference in hospital mortality in the two groups between males and females. Kaplan–Meier curves show that there was no significant difference in the 5-year cardiac mortality between males and females belonging to the CABG and CABG + CE groups. CONCLUSION: The results of this study show that there was no significant difference in the short- and long-term outcomes of off-pump CABG and CE in both genders although women tend to carry a greater risk.